Glutathione Sulfhydryl (GSH) and Malondialdehyde (MDA) Levels Comparison in Senile Cataract Lenses of Coastal and Mountain Populations - Hidayat, Muhammad; Primasakti, Pattih (Jurnal Kedokteran Brawijaya, 2026)
Cataracts are a leading cause of global blindness, affecting over 20 million individuals, according to the WHO are primarily age-related but are influenced by UV radiation-induced oxidative stress on lens proteins and cells. Geographic UV intensity variations prompted further comparative studies Glutathione Sulfhydryl (GSH) and Malondialdehyde (MDA) in senile cataracts. This was a cross-sectional study. utilized all senile cataract patients who underwent extracapsular cataract extraction (ECCE) surgery. Lens nucleus specimens were examined for GSH and MDA levels at the Biomedical Laboratory of the Faculty of Medicine and Andalas University. The examination results were processed and analyzed using Pearson’s correlation test. The study included 32 participants, with the majority (68.8%) being men, primarily working as farmers (56.3%), and 81.3% having mature cataracts. No significant differences were found in GSH and MDA levels between residents living in coastal areas and those living in mountainous areas, with p-values of 0.087 and 0.484, respectively (p>0.05). There was no correlation between GSH and MDA levels in patients with senile cataracts living in coastal and mountainous areas or in those living solely in coastal or mountainous areas (p>0.05). There was no correlation between GSH and MDA levels in patients with senile cataracts living in coastal and mountainous areas. The decrease in GSH levels was due to aging and was not influenced by UV exposure. The average MDA levels in mountain residents were higher than those in coastal residents. UV radiation in mountainous areas induced more ROS, resulting in slightly higher MDA levels than in coastal areas.